2003
DOI: 10.1073/pnas.0930352100
|View full text |Cite
|
Sign up to set email alerts
|

Cell division pattern influences gene expression in the shoot apical meristem

Abstract: The shoot apical meristem of angiosperms shows a highly conserved cellular architecture in which a change of cell division orientation correlates with early events of leaf initiation. However, the causal role of this altered cellular parameter in leaf formation is debatable. We have used the dynamin-like protein phragmoplastin as a tool to modify the pattern of cell division within the apical meristem. Taking a microinduction approach, we show that local alteration in cell division orientation is not sufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 29 publications
3
25
0
Order By: Relevance
“…Precise control of transcription is achievable using inducible promoters in combination with microinduction, where the chemical inducer is embedded in a paste and applied under the microscope [53]. Microinduction has been used in combination with a tetracycline-inducible promoter driving expression of expansin and phragmoplastin, enabling control of gene expression in small areas within the meristem [53,54]. Among the inducible systems, the alcohol-inducible switch -based on components of the alc regulon, including AlcR transcriptional activator and alcA promoter of Aspergillus nidulans [55] -has been considered as one of the most promising in a wide range of model and crop plants.…”
Section: Inducible Promotersmentioning
confidence: 99%
“…Precise control of transcription is achievable using inducible promoters in combination with microinduction, where the chemical inducer is embedded in a paste and applied under the microscope [53]. Microinduction has been used in combination with a tetracycline-inducible promoter driving expression of expansin and phragmoplastin, enabling control of gene expression in small areas within the meristem [53,54]. Among the inducible systems, the alcohol-inducible switch -based on components of the alc regulon, including AlcR transcriptional activator and alcA promoter of Aspergillus nidulans [55] -has been considered as one of the most promising in a wide range of model and crop plants.…”
Section: Inducible Promotersmentioning
confidence: 99%
“…Studies of mutations with pleiotropic effects frequently describe morphological or cellular changes in the leaves, whereas the effect on other shoot organs, especially the different floral organs, is treated less profoundly (Hu et al, 2003;Smith et al, 1996;Tsuge et al, 1996;Tsukaya, 2003;Wyrzykowska et al, 2002;Wyrzykowska and Fleming, 2003). We review below some of the genes for which detailed descriptions of floral phenotypes are available.…”
Section: Genes That Affect Floral Organ Sizementioning
confidence: 99%
“…Recent growth models of Antirrhinum petal lobes reveal that the generation of asymmetric shape depends on the direction of growth rather than on regional differences in growth rates (Rolland-Lagan et al, 2003). It has been shown that the induction of non-anticlinal divisions in the tunica layers of tobacco shoot apices leads to alterations in key regulators of SAM maintenance but fails to induce morphogenesis (Wyrzykowska and Fleming, 2003). However, it can be argued that the maintenance of structured anticlinal divisions in the tunica layer, such as the ones described in this study, might be essential for morphogenesis to occur.…”
Section: Cell Behavior and Primordium Developmentmentioning
confidence: 99%